MODERN TRENDS OF SUBURBANIZATION: SPECIFIC FEATURES OF LOW-RISE RESIDENTISAL DEVELOPMENT AREAS IN THE SUBURBAN AREA OF LVIV - Stets, Igor (Theory and practice of design, 2025)
The article examines modern trends in the development of low-rise residential housing in the suburban area of Lviv as one of the key forms of suburbanization processes. The study is based on the analysis of the historical stages of suburban area formation, spatial patterns of the distribution of residential complexes, and the specific features of their functional structure. Special attention is paid to identifying the typological characteristics of low-rise residential development, the level of its infra- structural development, and its impact on the socio-economic growth of surrounding communities. Purpose. The purpose of this study is to analyze the specific features of low-rise residential development in the suburban area of Lviv as one of the key forms of suburbanization processes. Methodology. The research applies a comprehensive approach that includes a historical and retrospective analysis of suburban development, typological analysis of low-rise residential housing, spatial mapping using geoinformation data, and a comparative analysis of functional and planning characteristics of different types of residential complexes. Results. The study establishes the evolution of suburban development from Soviet-era garden cooperatives to modern organized low-rise residential settlements. It identifies the dominance of terraced housing typologies and small-scale complexes of up to 20 residential units. Spatial patterns in the distribution of res- idential settlements were revealed – concentration along major transport routes (Solonka, Sokilnyky, Zubra) and within recreational zones (Bryukhovychi). The study also highlights the problem of imbalance between residential and public functions, social isolation of most complexes, as well as both the positive and negative impacts of low-rise residential development on the territories of local communities. Scientific novelty. For the first time, the functional and spatial development features of low-rise residential areas within the suburban zone of Lviv have been systematically analyzed. The main typological characteristics, functional-spatial models, and urban as well as socio-economic implications for suburban territories have been identified. Practical relevance. The obtained results can be used in developing a sustainable development strategy for the suburban zone of Lviv, particularly for: – improving functional and spatial planning schemes of such territories, taking into account the processes of low-rise residential construction as an important com- ponent of the housing structure within the area influenced by a large city in a market economy; – formulating recommendations for the balanced development of residential, public, and recreational functions within low-rise residential areas.